2019
DOI: 10.1093/mnras/stz2225
|View full text |Cite
|
Sign up to set email alerts
|

Thermally driven wind as the origin of warm absorbers in AGN

Abstract: Warm absorbers are present in many Active Galactic Nuclei (AGN), seen as mildly ionised gas outflowing with velocities of a few hundred to a few thousand kilometres per second. These slow velocities imply a large launch radius, pointing to the broad line region and/or torus as the origin of this material. Thermal driving was originally suggested as a plausible mechanism for launching this material but recent work has focused instead on magnetic winds, unifying these slow, mildly ionised winds with the more hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 58 publications
2
38
0
Order By: Relevance
“…The thermal wind models predict that the column density of the wind is roughly proportional to the mass accretion rate of the central SMBH (Kallman & Dorodnitsyn 2019;Done et al 2018). Owing to its slow velocity and mild level of ionization, several works have suggested a thermal origin of the WA, having a large launch radius extending beyond BLR and/or torus (Krolik & Kriss 1995Dorodnitsyn et al 2008;Mizumoto et al 2019). Thermal winds are highly sensitive to the irradiating SED, and that serves as an important factor in constraining the parameters (Dyda et al 2017).…”
Section: The Origin and Acceleration Mechanisms Of The Ionized Outflowsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal wind models predict that the column density of the wind is roughly proportional to the mass accretion rate of the central SMBH (Kallman & Dorodnitsyn 2019;Done et al 2018). Owing to its slow velocity and mild level of ionization, several works have suggested a thermal origin of the WA, having a large launch radius extending beyond BLR and/or torus (Krolik & Kriss 1995Dorodnitsyn et al 2008;Mizumoto et al 2019). Thermal winds are highly sensitive to the irradiating SED, and that serves as an important factor in constraining the parameters (Dyda et al 2017).…”
Section: The Origin and Acceleration Mechanisms Of The Ionized Outflowsmentioning
confidence: 99%
“…The possibility of thermally driven winds have been investigated in stellar mass black hole binaries and NS binary systems and have been found to explain the outflows well (see for e.g., Done et al 2018;Tomaru et al 2019), or sometimes in a hybrid form incorporating both MHD and thermal winds (Waters & Proga 2018). The idea of having hybrid acceleration mechanisms active has also been extended to AGN (Dorodnitsyn et al 2008;Mizumoto et al 2019), where the Compton temperature of the wind has been tracked as a function of M BH and λ Edd , and a combination of thermal and radiation pressure acting on dust have been suggested to drive the WA outflows.…”
Section: The Origin and Acceleration Mechanisms Of The Ionized Outflowsmentioning
confidence: 99%
“…Assuming that the outflow velocities of the warm absorbers correspond to the escape velocities from the gravitational potential of the SMBH, they are likely to be launched from outer accretion disks and/or torus regions. Mizumoto et al (2019) have shown that the warm absorbers can be explained as thermally-driven winds from the broad line region and torus (see e.g., Krolik & Kriss 1995 for earlier works). However, they assume a very simplified geometry, whereas the real structures of the interstellar medium in the central region of AGNs are still unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Padovani 2017;Jarvis et al 2019). The three most likely ways in which AGNs can generate radio emission are: (i) synchrotron emission from jets (Kukula et al 1998;Kharb et al 2015Kharb et al , 2017, (ii) coronal emission (Laor & Behar 2008;Behar et al 2018), and (iii) synchrotron from electrons accelerated at non-relativistic shocks that may result from wide angle sub-relativistic quasar winds (Nims, Quataert & Faucher-Giguère 2015;Zakamska et al 2016a), with magnetocentrifugal winds (Blandford & Payne 1982;Everett 2005;Fukumura et al 2010), thermally driven AGN winds (Begelman & McKee 1983;Woods et al 1996;Mizumoto et al 2019), or any combination of the above also being possibilities. In this paper, we identify sources in the Quasar Feedback Survey sample where AGN processes contribute significantly to the radio emission and do not attempt to distinguish between the different AGN-related mechanisms.…”
mentioning
confidence: 99%